Confirming the Causative Role of Acetaminophen in Indeterminate Acute Liver Failure Using Acetaminophen-Cysteine Adducts - Frey, Sean M. (J Med Toxicol, 2015)
INTRODUCTION: Acetaminophen-cysteine adducts (APAP-CYS) are a serum biomarker of acetaminophen exposure, formed when the oxidative metabolite of acetaminophen binds to cysteine residues of hepatic proteins. APAP-CYS adducts become elevated in cases of acute liver failure following acetaminophen overdose and have been proposed as a diagnostic tool to identify acetaminophen-induced acute liver failure when standard testing is inconclusive. CASE REPORT: A 26-year-old female with history of unexplained, severe hepatitis presented with a second episode of severe hepatitis including coagulopathy and transaminase levels >10,000 U/L. The patient reported ingesting “only a couple” of acetaminophen tablets several days prior to her presentation. An acetaminophen concentration of 14 mcg/mL at presentation aroused suspicion that acetaminophen might have caused the patient’s liver failure, despite her adamant denial of overdose. APAP-CYS adduct levels measured from serum obtained 4 days after her presentation and in two consecutive serum samples are reported alongside previously reported APAP-CYS levels. DISCUSSION: The patient’s APAP-CYS adduct levels were consistent with those seen in acute liver injury due to acetaminophen toxicity, even up to 1 week following presentation, and allowed for confirmation of acetaminophen toxicity as the cause of the her hepatitis. Overall, this case demonstrates the real-time application of APAP-CYS adducts as a biomarker to diagnose acetaminophen toxicity in patients with indeterminate acute liver failure.